Constitution writing, religion and democracy - Bâli, Aslı Ü.; Lerner, Hanna ca. 20./21.Jh. (Cambridge University Press, 2017)
Introduction / Asli U. Bali and Hanna Lerner -- The curious case of religion in the Norwegian Constitution / John Madeley -- Religion and the Japanese Constitution / Helen Hardacre -- Constitution making and religion in West Germany in the shadow of state failure / Tine Stein -- Secularism in a sectarian society : the divisive drafting of the 1926 Lebanese Constitution / Mark Farha -- The Constitution of a "laic" African and Muslim country : Senegal / Soulaymane Bachir Diagne -- Constitution writing and religious divisions in Turkey / Ergun Ozbudun -- Constitutionalism, Islamic law, and religious freedom in post-independent Indonesia / Mirjam Kunkler -- Cross-cutting rifts in constitutions and minority rights : India, Pakistan, Sri Lanka / Shylashri Shankar -- Islamic law in an Islamic Republic : what role for parliament? / Matthew Nelson -- Constitutional impasse, democracy and religion in Israel / Hanna Lerner -- Islam and constitutionalism in the Arab world : the puzzling course of Islamic inflation / Nathan Brown -- The politics of sacred paralysis : Islam in recent Moroccan and North African constitutions / David Mednicoff -- Dancing by the cliff : constitution writing in post-revolutionary Tunisia, 2011-2014 / Nadia Marzouki -- Designing constitutions in religiously divided societies / Asli U. Bali and Hanna Lerner